Correlation between pierced earrings and the prevalence of metal allergies at Tokushima university hospital: a 15-year retrospective analysis - Toyoko Tajima; Maki Hosoki; Mayu Miyagi; Miho Inoue; Aya Ozawa; Mizuki Shinkai; Mio Naritani; Yoshiaki Kubo; Swarnalakshmi Raman; Parimal Ravindra Chavan; Kazuyuki Koike; Yoshizo Matsuka (Scientific Reports)
Abstract In Japan, metal allergies are becoming increasingly prevalent, raising concerns for public health. This study examined metal allergy characteristics, patient histories, and clinical signs associated with patch test results over a 15-year period at the Dental Metal Allergy Clinic of Tokushima University Hospital. A retrospective analysis of 1085 patients revealed that 65.4% tested positive for at least one metal allergen, with palladium chloride, nickel sulfate, potassium dichromate, and cobalt chloride identified as the most common allergens. Female patients were disproportionately affected, accounting for 78.4% of the study population. Notably, there was a substantial increase in patients reporting inflammation due to pierced earrings, increasing from 5.0% in 2005 to 43.2% in 2020, particularly among females. Patients with a history of inflammation from earrings had an 81.3% prevalence of metal allergies, which was significantly higher than the 60.4% reported in those without such a history (chi-square test, p < 0.001). These findings suggest a strong link between earrings and metal allergies, underscoring the need for improved education, early detection, and preventive strategies to address the growing impact of metal allergies on public health.